Cancellation of Overlapping Land Rights Certificates Without Judicial Mechanism - Hermanta, I Gede; Suwitra, I Made; Alit Puspadma, I Nyoman (Jurnal Indonesia Sosial Sains, 2026)
Land title certificates are administrative state products that serve as strong evidentiary instruments to ensure legal certainty in land law. However, the issuance of overlapping certificates persists in practice, creating disputes and legal uncertainty. This research aims to analyze the authority of the National Land Agency in canceling overlapping land title certificates and to assess the extent to which such cancellations provide legal certainty. It also examines BPN’s responsibility arising from such cancellation, particularly in relation to good-faith certificate holders. This research employs a normative legal method using statutory and conceptual approaches, analyzed through interpretative legal reasoning. The findings indicate that the authority to cancel overlapping land title certificates, exercised by the Head of the Regional Land Office and, in certain circumstances, by the Minister of Agrarian Affairs and Spatial Planning/National Land Agency, constitutes a lawful delegation and substitution of authority as an administrative corrective mechanism. Nevertheless, the existence of substantively identical authority across different hierarchical levels without clear limitations, combined with the absence of temporal restrictions on administrative cancellation, results in a form of legal certainty that remains relative and nonfinal, as such decisions may still be subject to judicial review. Furthermore, BPN’s authority in the administrative cancellation of overlapping certificates is limited to the administrative domain and lacks adequate compensation mechanisms for good-faith holders, thereby failing to achieve substantive justice. This study recommends clearer delineation of cancellation authority and explicit mechanisms for legal protection and remedies to strengthen legal certainty and justice in land administration.